2017
DOI: 10.17015/ejbe.2017.020.07
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Non-Performing Loan in South Asia: The Role of Financial Crisis

Abstract: The purpose of the study is to recognize the factors influencing non-performing loan in banking system of South Asian region for the period of [1999][2000][2001][2002][2003][2004][2005][2006][2007][2008][2009][2010][2011][2012][2013][2014][2015]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…If a variable cannot be affected by shock, then the specific shock can not be known but shock in general (Zuhroh et al, 2017). This result is similar to the finding from a study of Rehman (2017) which shows that the impulse response function confirms the NPL impacted on main bank indicators, one of them is ROE, ETA, and LG. The impacts to bank indicators even bigger than macroeconomic indicators.…”
Section: Impulse Response Function (Irf) Testsupporting
confidence: 83%
“…If a variable cannot be affected by shock, then the specific shock can not be known but shock in general (Zuhroh et al, 2017). This result is similar to the finding from a study of Rehman (2017) which shows that the impulse response function confirms the NPL impacted on main bank indicators, one of them is ROE, ETA, and LG. The impacts to bank indicators even bigger than macroeconomic indicators.…”
Section: Impulse Response Function (Irf) Testsupporting
confidence: 83%
“…En la región sur de Asia, Rehman (2017), detectó que los bancos experimentaron una gran pérdida de activos y reservas de capital, debido al rápido aumento de los préstamos morosos y, en consecuencia, afectó la actividad económica, durante el periodo de 1999-2015. Evidenció que la calidad de la gestión del banco (medida por la rentabilidad), mantiene una relación inversa con el nivel de morosidad.…”
Section: Análisis De Los Factores En Asia Y áFricaunclassified
“…Previous studies on non-performing loans (NPL) showed that NPL has negative effect on economic growth (see Erdoğdu, 2017;Balgova et al, 2018). Studies on NPL also analyzed factors influenced level of NPL (see Makri et al, 2014;Rehman, 2017;Waqas et al, 2019).…”
Section: R E S E a R C H O B J E C T I V E Smentioning
confidence: 99%